2018
DOI: 10.1186/s12882-018-1075-2
|View full text |Cite
|
Sign up to set email alerts
|

Meeting patients where they are: improving outcomes in early chronic kidney disease with tailored self-management support (the CKD-SMS study)

Abstract: BackgroundTo achieve optimal health outcomes, people with chronic kidney disease must make changes in their everyday lives to self-manage their condition. This can be challenging, and there is a need for self-management support interventions which assist people to become successful self-managers. While interventions have been developed, the literature in this area is sparse and limited by lack of both individualisation and sound theoretical basis. The aim of this study was to implement and evaluate the Chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 61 publications
0
30
1
Order By: Relevance
“…The level of activation and ability to self-manage conditions play an important role in patient's overall health and wellbeing, especially for those presenting with multimorbidity [20,22]. There is a growing body of evidence indicating that patients who are actively engaged in health care system have improved health-related quality of life and clinical outcomes [23][24][25]. In addition, patients with high activation levels are often empowered through shared decision-making with their GPs and are reported to have better adherence to treatment regimens and lower hospital admissions compared to patients with lower activation scores [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The level of activation and ability to self-manage conditions play an important role in patient's overall health and wellbeing, especially for those presenting with multimorbidity [20,22]. There is a growing body of evidence indicating that patients who are actively engaged in health care system have improved health-related quality of life and clinical outcomes [23][24][25]. In addition, patients with high activation levels are often empowered through shared decision-making with their GPs and are reported to have better adherence to treatment regimens and lower hospital admissions compared to patients with lower activation scores [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…2 Self-management, a complex set of processes that involves acquiring knowledge, skills and confidence to manage a chronic disease, 3 has the potential to positively affect clinical outcomes and quality of life for patients with chronic kidney disease. 4 There is the opportunity to involve patients in the development of self-management support interventions that meet their needs, specifically around the areas of knowledge, how they receive knowledge and timeliness of the information. 5 Traditionally, self-management interventions for patients with chronic kidney disease have included education and support through face-to-face interactions, with minimal use of electronic health (e-health) tools (e.g., websites, mobile apps, short-messaging service).…”
Section: Openmentioning
confidence: 99%
“…Patient-focused research can help identify priorities and outcomes that are important to patients and can enable the development of care components that can improve health care practice [ 4 - 6 ]. This information has also driven the development of tools that can promote self-management, which has been shown to slow disease progression, specifically in patients with CKD [ 5 , 7 ]. While qualitative studies have identified specific topics of importance to patients with respect to disease management [ 4 , 5 ], there is still an outstanding need for information directly from patients about their experience of symptoms and outcomes in CKD [ 8 - 10 ].…”
Section: Introductionmentioning
confidence: 99%